Multinodular and vacuolating neuronal tumor affecting amygdala and hippocampus: A quasi‐tumor?. Issue 1 (7th December 2015) - Yamaguchi, Maki; Komori, Takashi; Nakata, Yasuhiro; Yagishita, Akira; Morino, Michiharu; Isozaki, Eiji
Abstract : Multinodular and vacuolating neuronal tumors (MVNT) have been referred to as distinctive neuronal tumors whose characteristic features include multiple nodules localized in the subcortical white matter. MVNT are composed of vacuolating dysplastic neurons reactive to HuC/HuD. A significant overexpression of alpha‐internexin (INA) limited to the stroma of nodules was reported in one tumor. Since genetic analyses have failed to demonstrate any consistent alterations, the nosological position as well as the nature of MVNT, namely, neoplastic or dysplastic, remains unclear. We herein present another example of MVNT involving the amygdala and anterior hippocampus in a 41‐year‐old man. In addition to the nodular lesions described earlier, we found INA‐positive ribbon‐like lesions that replaced neuropil and extended along the hippocampal gray matter. We also identified dysplastic neurons infiltrating into the CA4 hilus of the hippocampus. Intense INA expression was present in the stroma as well as the cytoplasmic membrane of dysplastic neurons and their processes. While the invasiveness suggested a neoplasm, a relatively restrictive, either nodular or ribbon‐like growth pattern with INA‐positive abnormal neuropil suggested a hamartoma. Such quasi‐tumors should be accommodated in the World Health Organization classification of tumors of the central nervous system, as are dysembryoplastic neuroepithelial tumor and Lhermitte‐Duclos disease.